Application of metacognitive strategies in the developmentof emotional and motivational self-regulationof students with special educational needs.Research on children with ADHD - Kajka, Natalia; Kulik, Agnieszka (Current Problems of Psychiatry, 2021)
The aim of the presented study is to verify whether the visual methods (Mind Maps and Sketch-noting) considered as metacognitive strategies will help to strengthen emotional and motivational self-regulation in children with ADHD. In this experimental study, 135 participants took part, including 45 primary school students diagnosed with attention deficit hyperactivity disorder with the presentation of mixed symptoms (M = 10.41; SD = 1.42), their parents (N = 45) and teachers (N = 45). The results obtained in the study indicate that after 25 training sessions with the use of both Mind Maps and Sketch-noting, children with ADHD make significantly fewer errors than during the first measurement. However, only in the Sketch-noting group did their average reaction time increase significantly, which indicates that they are more reflective. The presented metacognitive strategies can be successfully applied at school by students with ADHD and constitute a source of support for both students and teachers.